Student workbook to accompany medical assisting - Kathryn Booth (McGraw-Hill, 2009)
Respected for its inclusive coverage of AAMA, AMT, NHA, RMA, NOCTI, CAAHEP and SCANS, Booth's fourth edition now provides the 2010 ABHES and 2008 CAAHEP standards in each chapter! Preparation for Certification Boxes have been added to this edition to focus students on the specific exam they will take. Over 30 Electronic Health Record activities are incorporated into the text and available online through SpringCharts, simulating real patient encounters. Emergency Preparedness, additional administrative coverage and a completely revised workbook that now includes competency work products have been added for the 4th edition